Targeting Lymphotoxin Receptor Classical NFkB Signaling Facilitates Inflammation Resolution. (July 2018) - Piao, Wenji; Xiong, Yanbao; Li, Lushen; Saxenauni, Vikas; Wagner, Chelsea; Bromberg, Jonathan S
Abstract : Background: Contact hypersensitivity (CHS) reaction is a reliable model to assess immune cell-mediated cutaneous inflammatory response. This reaction is divided into three phases of antigen priming/sensitization, elicitation, and resolution, mirroring many aspects of allogeneic immune responses. Specific modulators of immune cell migration at each of the immune phases are not defined. Immune cell recruitment to the site of antigen challenge during the individual phases is required for CHS, however, the molecular mechanisms that regulate leukocyte trafficking are not fully understood. The lymphotoxin (LT) -LT beta receptor (LTβR) signal axis regulates lymphatic function and transendothelial migration of leukocytes across lymphatic vessels during homeostatic and inflammatory immune response. We hypothesized that inhibition of the distinct NFκB signaling pathways of the LTβR could regulate CHS reaction. Methods: Decoy receptor peptides that specifically inhibited the classical pathway of LTβR-NFkB signaling were designed and administered in vitro or in vivo at different phases. T cell and dendritic cell (DC) migration were assessed with in vitro and in vivo assays. Mice were sensitized with the hapten 2, 4-dinitrofluorobenzene (DNFB). The CHS response was assessed by tissue responses (ear swelling) and immunohistochemistry. Results: Targeting LTβR-classical NFκB pathway enhanced DC migration across lymphatic endothelium in in vitro. Administration of a decoy peptide which inhibits LTβR-mediated classical NFκB signaling at the time of hapten sensitization augmented the CHS inflammatory response, with increased local infiltration of T cells and DC at the hapten challenged tissues. This result was due to increased DC migration to draining lymph nodes, which enhanced T cell priming. Treatment with decoy peptide at the time of antigen challenge and elicitation inhibited CHS with reduced ear swelling and fewer CD3 + T cells and CD11C + DCs infiltrating the inflamed tissues. This effect was due to enhanced egress of T cells and DCs out of the tissues. Administration of the decoy peptide at the time of inflammatory resolution promoted tissue quiescence, with reduced numbers of DCs and T cells infiltrating the hapten challenged tissues, again as a result of enhanced migration out of the site of antigen deposition. Conclusions: LTβR-mediated classical NFκB signaling regulates inflammatory responses through regulation of lymphatic vessel function and transendothelial migration of T cells and DCs. Targeting the classical arm of LTβR signaling in lymphatic endothelium facilitates inflammatory resolution of CHS. This decoy peptide is a novel intervention to regulate immune cell migration and responses during distinct phases of the inflammatory response, and serves as a proof of concept for building unique therapeutic molecules to guide immune responses. NIH 1RO1 AI062765 and Maryland Living Legacy Foundation (LLF).